The impact of generic-only drug benefits on patients' use of inhaled corticosteroids in a Medicare population with asthma - Newhouse Joseph P; Brand Richard; Tager Ira B; Fung Vicki; Hsu John (BMC, 2008)
Abstract Background Patients face increasing insurance restrictions on prescription drugs, including generic-only coverage. There are no generic inhaled corticosteroids (ICS), which are a mainstay of asthma therapy, and patients pay the full price for these drugs under generic-only policies. We examined changes in ICS use following the introduction of generic-only coverage in a Medicare Advantage population from 2003-2004. Methods Subjects were age 65+, with asthma, prior ICS use, and no chronic obstructive pulmonary disorder (n = 1,802). In 2004, 74.0% switched from having a $30 brand-copayment plan to a generic-only coverage plan (restricted coverage); 26% had $15-25 brand copayments in 2003-2004 (unrestricted coverage). Using linear difference-in-difference models, we examined annual changes in ICS use (measured by days-of-supply dispensed). There was a lower-cost ICS available within the study setting and we also examined changes in drug choice (higher- vs. lower-cost ICS). In multivariable models we adjusted for socio-demographic, clinical, and asthma characteristics. Results In 2003 subjects had an average of 188 days of ICS supply. Restricted compared with unrestricted coverage was associated with reductions in ICS use from 2003-2004 (-15.5 days-of-supply, 95% confidence interval (CI): -25.0 to -6.0). Among patients using higher-cost ICS drugs in 2003 (n = 662), more restricted versus unrestricted coverage subjects switched to the lower-cost ICS in 2004 (39.8% vs. 10.3%). Restricted coverage was not associated with decreased ICS use (2003-2004) among patients who switched to the lower-cost ICS (18.7 days-of-supply, CI: -27.5 to 65.0), but was among patients who did not switch (-38.6 days-of-supply, CI: -57.0 to -20.3). In addition, restricted coverage was associated with decreases in ICS use among patients with both higher- and lower-risk asthma (-15.0 days-of-supply, CI: -41.4 to 11.44; and -15.6 days-of-supply, CI: -25.8 to -5.3, respectively). Conclusion In this elderly population, patients reduced their already low ICS use in response to losing drug coverage. Switching to the lower-cost ICS mitigated reductions in use among patients who previously used higher-cost drugs. Additional work is needed to assess barriers to switching ICS drugs and the clinical effects of these drug use changes.